PENERAPAN MEDIA PEMBELAJARAN WORD WALL DALAM MENINGKATKAN KEMAMPUAN KOSAKATA BAHASA JEPANG TERHADAP SISWA KELAS XI SMAN 9 PEKANBARU - Fitri, Neci Selvia; Widiati, Sri Wahyu; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research is about the application of learning media word wall in order to improve the students on japanese vocabulary. This research took place in senior high school of SMAN 9 Pekanbaru. The purpose of this research is to know how the procedures are being implemented and to know the degree of improvement by using media word wall. This research is a Classroom Action Research (CAR). The object of this research is was students of grade XI IPA 1 Senior High School of SMAN 9 Pekanbaru as many as 35 persons. This research is conducted in two cycles. The design used is the designed introduced by Kemmis & Mc. Taggart which the research flow includes steps such as: 1) planning, 2) acting, 3) observing, 4) reflecting. The data collection techtiques used are observation, field note, test on each cycle and documentation. On the cycle I, the result is 66%, on the cycle II increased into 77,14%. It can be concluded that the application of learning word wall media in order to improve the students on japanese vocabulary to student grade XI IPA senior high school of SMAN 9 Pekanbaru.Keywords : Vocabulary.Word Wall, Classroom Action Research.